Odpowiedzi

2010-01-09T17:40:17+01:00
(3a-6b) + (9a-5+b) = 12a - 5b - 5
x²+ (2x²-1+x)+x = 3x²+2x-1
(6z - 4z²) + (-5z +6z²)= 2z²+z
5/6a² + (3/4a - 1/6a²) + a = 4/6a² + 7/4a
  • Roma
  • Community Manager
2010-01-09T17:42:36+01:00
E) (3a - 6b) + (9a - 5 +b) = 3a - 6b + 9a - 5 + b = 12a - 5b - 5

f) x kw + (2x kw - 1 +x) + x) = x² + (2x² - 1 + x) + x = x² + 2x² - 1 + x + x = 3x² + 2x - 1

g) (6z - 4z kw) + (-5z +6z kw) = (6z - 4z²) + (-5z + 6z²) = 6z - 4z² -5z + 6z² = 2z² + z

h) 5/6a kw + (3/4a - 1/6a kw) + a = 5/6a² + (3/4a - 1/6a²) + a = 5/6a² + 3/4a - 1/6a² + 4a²/4a = 4/6a² + 7/4a = 2/3a² + 7/4a